Textbooks Transformation Into Digital Comics As Innovative Learning Media for Social Science Studies in Junior High School - Krisna Dwiputra, Dimas Febriansyah; Budiyanto, Tasya Mutiara; Adz Dzakiyyah, Tsamarah; Iqbal, Muhamad (Universitas Pendidikan Indonesia, 2020)
The utilisation of comics as learning media to elevate students' interest towards social science studies is not an unfamiliar phenomenon. However, based on the literature review written by the author, it is known that the existing social science comics still have shortcomings, namely, first, the content materials only cover economic-themed comics, even though social science studies at junior high school level or MTs is an integrated learning which is supposed to integrate the concepts of geography, sociology, economics and history in the learning process; and second, social science comics are less efficient in terms of cost, as it is still available in the conventional form (printed form). Hence, this study is aimed to address this gap through the transformation of existing textbooks into comic textbooks in the form of a platform called Line Webtoon as learning media for social science studies. The inquirer conducted a literature review of 43 selected articles from the year of 2016 to 2020 from Q1-Q3 and S1-S3 accredited journals, then the inquirer focused on conducting a study of the use of comics and textbooks as learning media. This study indicates that transforming textbooks into digital comics results in an excellent learning media innovation to enhance students’ motivation in the learning process of social science studies. Overall, this study provides an appropriate suggestion for further research on the effectiveness of utilising KOBUT IPS in the social studies learning process at junior high school level.